Remote sensing of salinity from satellite‐derived CDOM in the Changjiang River dominated East China Sea. Issue 1 (29th January 2013) - Bai, Yan; Pan, Delu; Cai, Wei‐Jun; He, Xianqiang; Wang, Difeng; Tao, Bangyi; Zhu, Qiankun
Abstract: [1] Defining highly variable freshwater plume area from space is important for characterizing the dynamics of biogeochemical properties and understanding the effects of climate change and human activities on plume‐related processes. The absorption coefficient of colored dissolved organic matter ( a CDOM ) from satellite ocean color data can be used to estimate the salinity and thus the plume area in coastal oceans if a robust conservative salinity and a CDOM relationship and an accurate satellite a CDOM algorithm can be established. In this paper, tight relationships between surface water salinity and in situ a CDOM were found during several cruises covering all seasons and the full salinity range in the East China Sea. Thus, a salinity inversion model from a CDOM was developed and validated with an independent data set, in which 73.6% of the data were within the absolute salinity error of ±1 and 87.1% were within ±1.5. Factors influencing the conservative behavior of colored dissolved organic matter are analyzed, with a particular focus on the effect of the phytoplankton‐induced autochthonous colored dissolved organic matter. In addition, several satellite a CDOM algorithms were compared and validated with our in situ data. Monthly satellite‐derived salinity images were mapped in August from 2008 to 2010 and showed the significant interannual variability in the plume coverage. This study demonstrated that the salinity derived from satellite‐derived a CDOM can provide a reliable and good synoptic view of the plume area, and help with biogeochemical studies, in particular, those properties related to the interannual variability of plume coverage, although the development of a localized satellite algorithm of a CDOM is still desirable. Key Points: Relationship between salinity and CDOM was analyzed using nine cruises data A salinity inversion model applicable to all seasons was developed in the ECS Satellite CDOM algorithms were validated by in situ data in the ECS